2017
DOI: 10.5507/bp.2017.035
|View full text |Cite
|
Sign up to set email alerts
|

Freezing of gait is associated with cortical thinning in mesial frontal cortex

Abstract: Aims.The relationship between freezing of gait (FOG) and regional brain atrophy has been intensively investigated, but it is still not clearly understood. The study objective was to test whether grey matter (GM) atrophy contributes to FOG in Parkinson´s disease (PD) using a surface-based algorithm. Methods. We investigated 21 patients with PD, 11 with FOG and 10 without FOG. Both groups were assessed using a FOG questionnaire and Hoehn and Yahr staging. High resolution T1-weighted brain images were acquired fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 45 publications
1
14
0
Order By: Relevance
“… Pietracupa et al (2017) found that PD patients with FOG exhibit significant changes in WM and cortical thinning of the mesial surface of the bilateral cerebral hemispheres. Vastik et al (2017) found that FOG was associated with regional GM atrophy in the mesial frontal and cingulate cortices. Consistent with our results, the thickness of the posterior cingulate cortex and the temporal cortex were correlated with H-Y stages.…”
Section: Discussionmentioning
confidence: 94%
“… Pietracupa et al (2017) found that PD patients with FOG exhibit significant changes in WM and cortical thinning of the mesial surface of the bilateral cerebral hemispheres. Vastik et al (2017) found that FOG was associated with regional GM atrophy in the mesial frontal and cingulate cortices. Consistent with our results, the thickness of the posterior cingulate cortex and the temporal cortex were correlated with H-Y stages.…”
Section: Discussionmentioning
confidence: 94%
“…(2015)17 PD-FOG (57±7) 21 PD-nFOG (47±9)VBMGM volumeGM loss in right cerebellum, medial frontal, precentral cortex, and left middle temporal gyrusNot performedMyers et al. (2017)25 PD-FOG (67±10) 38 PD-nFOG (64±10)VBMCerebellar volumesNo GM lossNo correlationVastik et al. (2017)11 PD-FOG (71±6) 10 PD-nFOG (69±10)SBMGM thicknessGM loss in left SMA, anterior cingulate cortex, temporal pole and right frontal operculumNo correlationBharti et al.…”
Section: Resultsmentioning
confidence: 99%
“…SBM provides cortical thickness and surface area measures (Fischl, 2012). Only two recent studies (Pietracupa et al., 2018; Vastik et al., 2017) have investigated possible GM changes in PD-FOG using the SBM technique and both demonstrated prominent cortical thinning in frontoparietal regions of the medial wall in PD-FOG.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations